2019
DOI: 10.5603/cj.a2017.0130
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of daytime heart rate, blood pressure, their products and quotients in chronic heart failure

Abstract: Diastolic blood pressure, SBP × HR and DBP × HR products may be useful in subsequent heart failure exacerbation risk stratification. Moreover, DBP value may predict short-term mortality in patients with CHF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Beyond the prognostic implication of HR, BP and their products in patients with stable CHF, attention was paid to the value of SBP and DBP itself, in terms of the golden ratio. In the study population, Kowalczys et al [1] found mean daytime SBP and DBP of patients with stable CHF as 114 mmHg and 70 mmHg, respectively. The ratio of SBP to DBP gives 1.62, which is very close to the golden ratio as described previously by the famous mathematicians Euclid and Fibonacci [2].…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…Beyond the prognostic implication of HR, BP and their products in patients with stable CHF, attention was paid to the value of SBP and DBP itself, in terms of the golden ratio. In the study population, Kowalczys et al [1] found mean daytime SBP and DBP of patients with stable CHF as 114 mmHg and 70 mmHg, respectively. The ratio of SBP to DBP gives 1.62, which is very close to the golden ratio as described previously by the famous mathematicians Euclid and Fibonacci [2].…”
mentioning
confidence: 88%
“…The article published by Kowalczys et al [1] was read with great enthusiasm and interest. Briefly, the prognostic value of daytime heart rate (HR), systolic (SBP) and diastolic (DBP) blood pressure (BP), and their multiplication products and ratios was assessed in congestive heart failure (CHF) patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Depression is one of the most important factors determining QoL in HF patients, this also contributes to social isolation [6,7]. Depressed mood and vital exhaustion are strong predictors of low life expectancy, all-cause and cardiovascular (CV) mortality, independent of classical risk factors [8][9][10][11][12]. Acute emotional stress has been linked to a high incidence of acute CV events, arrhythmias and sudden cardiac death [13].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, all patients were treated pharmacologically with drugs that affect blood pressure and heart rate, which may have had an impact on the potential prognostic value of the SBP/DBP ratio. Furthermore, the methodology of our study included only daytime multiple blood pressure measurements during hospitalization [11]. Meanwhile, Yetkin et Anna Kowalczys et al, Golden ratio in congestive heart failure al.…”
mentioning
confidence: 99%